UPAYA KEPALA SEKOLAH DALAM MENINGKATKAN PENGELOLAAN PERPUSTAKAAN DI SEKOLAH DASAR - Irawati (Universitas Negeri Padang, 2014)
The goal of this research are to see informations abaut headmaster to library organizing by school principal. The result of this research are the headmaster can to using library with efectiv and eficien by school principalin the state junior high school stay in good enough category. Kata kunci : Pengelolaan perpustakaan